Contrast sensitivity function with soft contact lens wear - Sapkota, Kishor (2020)
Purposes: To compare contrast sensitivity function (CSF) with soft contact lens (SCL) and spectacles wear. To investigate the effect of a three-month period of SCL wear on CSF.Methods: Forty-seven myopic subjects with no history of contact lens (CL) wear were included in this longitudinal prospective study. CSF was measured with spectacles using the CSV-1000 (VectorVision, Greenvile, OH). Subsequently, subjects were fitted with a daily disposable lens (Nelfilcon-A, Stenofilcon-A or Nesofilcon-A) in one eye and a monthly disposable lens (Lotrafilcon-B. Comfilcon-A or Balafilcon-A) in the other eye and wore the same type of CLs for three months. CSF was measured again on the same day and after three months wearing CLs. Differences in CSF with spectacles and CLs on baseline and changes to CSF after three months of CLs wear were assessed. The effect of lens materials and wearing modality on CSF change was also investigated.Results: CSF was higher with CLs in comparison to the values with spectacles for spatial frequencies of 3, 6 and 12 cycles per degree (cpd) (p<0.05) while there was no difference for spatial frequency of 18 cpd (p=0.114). No significant difference was found in the CSF with CLs between baseline and after three months of lens wear (p > 0.05). There was no difference in CSF between hydrogel and silicone CLs as well as when comparing daily with monthly wear CLs (p > 0.05).Conclusion: CSF is better with CLs than with spectacles. CSF values with CL are similar between =baseline and after 3 months of lens wear. (C) 2020 Spanish General Council of Optometry. Published by Elsevier Espana, S.L.U.